Predicting Teacher Performance Through Interpersonal Communication and Work Discipline: Evidence from Indonesian State Elementary Schools - Aziza Nursanti; Syarwani Ahmad; Djunaidi Djunaidi (Journal of Social Work and Science Education, 2026)
This study examines the influence of interpersonal communication and work discipline on teacher performance in Indonesian state elementary schools. Using a quantitative correlational design, data were collected from 70 teachers across four state elementary schools in Sako District, Palembang City, selected through simple random sampling from a population of 225 teachers. Questionnaires measuring interpersonal communication, work discipline, and teacher performance were administered, and data were analyzed using simple and multiple linear regression, t-tests, F-tests, and coefficient of determination (R²). The findings reveal that: (1) interpersonal communication positively and significantly influences teacher performance (t-value > t-table, p < 0.05); (2) work discipline positively and significantly influences teacher performance (t-value > t-table, p < 0.05); and (3) interpersonal communication and work discipline jointly account for 65% of the variance in teacher performance (R² = 0.65, F-value > F-table, p < 0.05). These results indicate that improving both interpersonal communication skills and work discipline among teachers can significantly enhance their professional performance. The study contributes empirical evidence on teacher performance determinants in the Indonesian elementary education context and offers practical implications for school principals, policymakers, and teacher professional development programs seeking to improve educational quality through targeted human resource management strategies.